2014
DOI: 10.5897/ijbc2013.0628
|View full text |Cite
|
Sign up to set email alerts
|

Population status, nesting sites and seasonal fluctuation of Egyptian vultures (Neophron percnopterus): Dynamics and implications for the species conservation in and around Jodhpur

Abstract: Nine species of vulture were reported in India. Out of them, four species Gyps indicus, Gyps bengalensis, Sacrogyps calvus and Neophron percnopterus are permanent residents and remain in and around Jodhpur. The remaining three species Gyps fulvus, Gyps himalayensis and Aegypus monachus are migratory species and come to site from October to February in winter season. Resident species reproduce here due to availability of food through out the year. Egyptian vulture is a smaller bird with naked head and without l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The maximum number of bird species and abundance during the wet season compared to the dry season may be due to the presence of high food sources, favorable weather conditions and occasionally high quality of nesting and breeding sites. Ramprakash and Purohit [ 61 ] conveyed that vultures abundance display high levels of seasonal variations to meet their requirement for nest, roost and food. Various researches indicated that seasonal changes leads variation in the availability of water and food resources, and consequently, birds change across habitats depending on their needs and accessibility of cover and food [ 16 , 20 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum number of bird species and abundance during the wet season compared to the dry season may be due to the presence of high food sources, favorable weather conditions and occasionally high quality of nesting and breeding sites. Ramprakash and Purohit [ 61 ] conveyed that vultures abundance display high levels of seasonal variations to meet their requirement for nest, roost and food. Various researches indicated that seasonal changes leads variation in the availability of water and food resources, and consequently, birds change across habitats depending on their needs and accessibility of cover and food [ 16 , 20 , 62 ].…”
Section: Discussionmentioning
confidence: 99%